2018
DOI: 10.5588/ijtld.17.0376
|View full text |Cite
|
Sign up to set email alerts
|

High rates of exposure to tuberculosis patients among HIV-infected health care workers in Botswana

Abstract: Setting and Objective We compared daily exposure to tuberculosis (TB) patients between HIV-infected and HIV-uninfected health care workers (HCWs), and examined uptake of antiretroviral therapy (ART) and isoniazid preventive therapy (IPT) among HIV-infected HCWs in Botswana. Design We conducted a cross-sectional study among HCWs in 30 hospitals and clinics. We determined self-reported exposure frequency to TB patients and HIV status through in-person interviews. HCWs with unknown or negative HIV status were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Because they meet the public on a daily basis, healthcare workers play a vital role, not merely in the betterment of DR-TB healthcare services, but also in developing and achieving TB strategic outcomes and translating DR-TB strategies into action [14,15]. On the other side, it is easy to anticipate that working in healthcare facilities, particularly having frequent and direct contact with DR-TB patients, increases the risk of infection among healthcare workers [16,17]. Cultural, social and economic factors that surround healthcare workers’ working environment affect their role in DR-TB management and control [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because they meet the public on a daily basis, healthcare workers play a vital role, not merely in the betterment of DR-TB healthcare services, but also in developing and achieving TB strategic outcomes and translating DR-TB strategies into action [14,15]. On the other side, it is easy to anticipate that working in healthcare facilities, particularly having frequent and direct contact with DR-TB patients, increases the risk of infection among healthcare workers [16,17]. Cultural, social and economic factors that surround healthcare workers’ working environment affect their role in DR-TB management and control [18].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings may inform planning of national CBE screening programming in Botswana and similar settings. Other research like [16] and [17] investigated exposure of HIV and TB of non-infected HIV people among HIV-infected people who have TB to determine infection rates within a community. COVID-19 research has also been conducted, however, there has only been one study by [18] as far as what has been identified that has used R programming for time series modelling of COVID-19 cases in Botswana in a 60-day period.…”
Section: Health Carementioning
confidence: 99%
“…All tests were two-tailed with a significance level of 0.05. Analysis was performed using Base R. [16] compared exposure to TB patients between HIV-infected and non-HIV infected health care workers (HCW) in health facilities in Botswana. Their statistical analysis was performed using Base R. No further details were revealed as to which functions were used for a specific operation.…”
Section: Base Rmentioning
confidence: 99%